Utilization of Sengon Wood Sawdust as Bio-Pellet Feedstock: Characteristics, Potential, and Feasibility for Renewable Energy - Setyawan, Eko Yohanes; Paepenan, Semuel Poumer (Politeknik Negeri Lhokseumawe, 2024)
The pellet-making process involves stages of drying, compaction, cooling, and size separation. Considering that Indonesia has great potential for biomass supply, this research aims to identify the characteristics of bio-pellets produced from sengon wood sawdust based on the pellet standard SNI8675:2018. The results showed that the highest calorific value at the Dry Basis (DB) condition was 4703 Kcal/kg, meeting national and international standards. The moisture content in the As Received (AR) condition was recorded at 10.36%, while the lowest ash content was 1.72%. The highest combustion rate was found in sample 3, with a value of 0.174 gr/min, indicating good combustion performance. The utilization of sengon wood sawdust as bio-pellets can be an efficient and environmentally friendly renewable energy solution, and has the potential to be further developed to support diversification and national energy security.